Pelatihan Koding dan Kecerdasan Artifisial (KKA) berbasis Scaffolded Approach bagi Guru SMA/SMK di Kabupaten Labuhanbatu Utara - Muhammad Halmi Dar; Denni M. Rajagukguk; Muhammad Iqbal Panjaitan (CV. Devi Tara Innovations, 2026)
The gap in technical and pedagogical competence among Information and Communication Technology teachers in regional areas in implementing the Coding and Artificial Intelligence curriculum posed a major challenge to supporting the digital transformation of education. This community service activity aimed to enhance the competence and self-efficacy of 20 secondary school teachers in Labuhanbatu Utara Regency through training based on the Technological Pedagogical Content Knowledge framework. The training was conducted over five days using a scaffolded approach that included learning management system orientation, plugged and unplugged hands-on practice, and contextual instructional design. The evaluation results demonstrated a significant improvement in participants' understanding, marked by an increase in the average score from 45.10 to 85.10, achieving a normalized gain average of 0.73, which fell into the high-effectiveness category. All participants successfully completed their portfolios and designed ready-to-use teaching modules. This scaffolded training proved effective in addressing the digital competence limitations of regional educators and strengthening their readiness for sustainable curriculum implementation.